Pengaruh Disiplin dan Motivasi Kerja Pegawai Terhadap Efektivitas Kerja Penanggulangan Bencana Alam di Kecamatan Sukamakmur Kabupaten Bogor - A.H. Rahadian; Mila Kencana (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
This study was conducted to analyze the Discipline and Employee Motivation to Work Effectiveness of the Natural Disaster Management in Sukamakmur District Bogor Regency.This study uses a quantitative explanatory to know how big the Discipline and Employee Motivation to Work Effectiveness of the Natural Disaster Management in Sukamakmur District Bogor Regency partial and multiple. The study population was all employees in the Regional Disaster Management Agency Bogor regency totaling 76 people, with a census method can be 76 samples and each respondent get as many questions as 33 statements using a Likert scale.Based on the results of data processing can result in a significant and positive influences of the Discipline and Employee Motivation to Work Effectiveness of the Natural Disaster Management in Sukamakmur District Bogor Regency. There is a positive and significant Employee Motivation to Work Effectiveness of the Natural Disaster Management in Sukamakmur District Bogor Regency. There is a positive and significant Discipline and Employee Motivation to Work Effectiveness of the Natural Disaster Management in Sukamakmur District Bogor Regency.